Three dimensional perfused cell culture for in vitro toxicity testing - Yang, J (2011)
This study describes the development of a novel method of three dimensional perfused cell culture for in vitro toxicity testing. Multiple parallel perfused microbioreactors (TissueFlexTM) were adopted to provide a well-controlled cell culture environment. Alginate and collagen type I, commonly used as hydrogel scaffolds to support cell culture, were tested as the scaffolding materials for this application. Alginate supports cell proliferation, but does not support cell attachment. Collagen gel (type I), good for cell attachment but with poor mechanical strength, could be used at the high concentration of 5mg/ml to prevent the degradation of the gel. Improvement of collagen biomechanical property by a purpose-designed compressor to physically induce cross-linking showed promising results and merits further study. The suitability of alamarBlue® assay, a common non-toxic non-destructive viability assay method, was confirmed for this study and the protocol was optimised. To demonstrate the effectiveness of three dimensional perfused cell culture, human mesenchymal stem cells (MSC) seeded in collagen type I were employed to test the cell inhibition of two antibiotics, trimethoprim and pyrimethamine. The results displayed the perfusion system has greater advantage and sensitivity than the static system, as does these of 3D scaffolds, compared with 2D. Such differences are related to the continuous supply of fresh culture medium to keep cells at a stable pH, temperature, oxygen, and a more physiological like environment. The cytotoxicity of two stereoisomer compounds, obtained confidentially from Pfizer. Ltd., was assessed using the developed method and compared to conventional 2D static and perfused culture by using rat adipose mesenchymal stem cells. The results successfully distinguished toxic and non-toxic compounds and also demonstrated that the 3D perfused system improved the prediction of drug toxicity over 2D culture. 3D perfused bioreactors were applied to hepatotoxicity study using freshly isolated rat hepatocytes. Only algimatrixTM supported hepatocyte spheroid formation among those tested including collagen type I, alginate beads, poly lactic acid fibres, and AlgimatrixTM. A new variation of TissueFlexTM bioreactor with micro-patterned surface, designed specifically for hepatocyte self-assembly culture without use of any scaffold, was tested. The results demonstrated that, compared with the standard sandwich culture, the self-assembly culture in the micro-patterned bioreactors showed high cell viability, biomarkers expression, as well as more physiological immunocytochemistry. Moreover, the differential gene expression indicated that self-assembly culture could provide more relevant information regarding metabolising processes than the 2D sandwich culture, which would potentially improve hepatotoxicity prediction. In conclusion, 3D perfused cell culture for in vitro toxicity testing improved the predictivity, reliability and physiological relevance of drug toxicity compared to traditional 2D culture.